Ordoliberalizem : teorija povezovanja prava in ekonomije - Hojnik, Janja (LeXonomica, 2020)
Ordoliberalism : theory of law and economics connecting. The article deals with theory of ordoliberalism, which is a less known theory of connecting law and economy into a single system of so-called economic constitution. It is a liberalistic theory of understanding market relations, nevertheless, it emphasises that freedom on the market is not to be achieved without legal intervention, considering that power of entities on the market differs and therefore more powerful entities restrict freedom and rights of the weaker – which results in monopolies, asymmetries of information and negative externalities. Ordoliberalism is a theory of authoritative liberalism that emphasises that law is an indispensable market accompanier, since it assures order on it. Theory of ordoliberalism is relevant also for EU market integration, because it advocates the need for strong supranational institutions, bound by the EU economic constitution, which replaces compartmentalized state market interventions. Članek obravnava teorijo ordoliberalizma, ki predstavlja manj znano teorijo povezovanja prava in ekonomije v enoten sistem, t. i. ekonomske ustave. Gre za liberalistično teorijo razumevanja odnosov na trgu, vendar poudarja, da se svoboda na trgu ne dosega brez posredovanja prava, saj moč vseh subjektov na trgu ni enaka in močnejši omejujejo svobodo in pravice šibkejših, kar se kaže preko monopolov, asimetrije informacij in negativnih eksternalij. Gre za teorijo avtoritativnega liberalizma v okviru katerega je pravo nujen spremljevalec trga, saj zagotavlja red na njem. Teorija ordoliberalizma je pomembna tudi za tržno integracijo EU, saj razlaga potrebo po močnih nadnacionalnih institucijah, vezanih na ekonomsko ustavo EU, ki zamenjujejo razdrobljeno državno poseganje na trg.